HAK ANAK NON MUSLIM TERHADAP HARTA ORANG TUANYA YANG MUSLIM (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2022)
This study aims to find out the right of non-muslim children to the property of their muslim parents. This research is normative legal research that uses a statutory approach and a conceptual approach, and uses primary and secondary legal sources. The technique of collecting legal materials is through literature study. The analysis used in this study uses a qualitative analytical method, namely by interpreting the legal materials that have been processed. In terms of the inheritance of different religions, the parties in it must submit to the religious law adopted by the heir who in this case the heir embraces Islam. Whereas Islamic inheritance law stipulates that a person with a religion other than Islam cannot inherit property from someone who is muslim, and vice versa, a person who is Muslim is not entitled to the inheritance of a person with a religion other than Islam. Children who have different religions with their parents can get a share of their assets from the heir but not as heirs but as people who are given a wasiat wajibah. Meanwhile, when the heir is still alive, non-muslim children still get property from their parents in the form of grants.